Book review: Coastline changes of the Baltic Sea from south to east. Past and future projection, edited by J. Harff, K. Furmańczyk, H. von Storch, 2017. Springer International Publishing. 388 pages, ISBN 978-3-319-49892-8. - Uścinowicz, Grzegorz (Geologos, 2020)
Book review: Coastline changes of the Baltic Sea from south to east. Past and future projection, edited by J. Harff, K. Furmańczyk, H. von Storch, 2017. Springer International Publishing. 388 pages, ISBN 978-3-319-49892-8.